Accessibility of services for early infant diagnosis of Human Immunodeficiency Virus in sub-Saharan Africa: a systematic review - Bwana, Veneranda M.; Frimpong, Christiana; Simulundu, Edgar; Mfinanga, Sayoki G.; Mboera, Leonard E.G.; Michelo, Charles (Tanzania Journal of Health Research, 2016)
Background: Early Infant Diagnosis (EID) of Human Immunodeficiency Virus (HIV) is one of the major interventions for HIV and AIDS in sub-Saharan Africa. However, the coverage is still lower than the recommended levels. The objective of this review was to systematically assess factors associated with accessibility of EID services in sub-Saharan Africa. Methods: Scientific engines were searched from library catalogues and public databases. The review included free full text articles in English published from 1996 to 2015 and fitting to the objectives of the study. Results: A total of 1,039,715 results appeared on the databases after initial searching. Of these, 48 eligible articles were identified and reviewed. From 2004 to 2014, the proportion of HIV exposed infants who received a virological test within the first 2 months of life in sub-Saharan Africa varied from 3 to 58%, far below the 80% recommended level by the World Health Organization. EID services were not available in more than 30% of health facilities in most sub-Saharan African countries. Factors associated with accessibility of EID services included parents with low formal education level, maternal unemployment, geographical relocation, religious beliefs, lack of paternal support, insufficient awareness of HIV control and prevention services, poor compliance to prevention of mother to child transmission services, lack of general knowledge of HIV transmission, stigma and discrimination, inadequate human resource for health, weak infrastructure, inadequate supplies of laboratory materials and late feedback of HIV test results. Conclusion: Availability and accessibility of EID services in sub-Saharan Africa is still low despite the investment made during the past decade. Both individual and institutional factors affect the availability and accessibility of the services. It is important that these factors are urgently addressed to improve EID services.